Comparative characteristics of the effectiveness of spinal anesthesia based on bupivacaine in combination with different intrathecal doses of dexmedetomidine - E.E. Shchegolkov; O.A. Loskutov (Медицина неотложных состояний, 2024)
Background. To increase the quality of a block, corresponding adjuvants are used intrathecally. However, currently, the interrelation between different doses of intrathecal dexmedetomidine as an adjuvant, differential analgesia, and the effectiveness of a spinal block is not adequately elucidated. The purpose: to conduct a comparative analysis on the effectiveness of motor (MB) and sensory block (SB), as well as to evaluate the clinical efficiency of analgesia during spinal anesthesia based on bupivacaine in combination with various intrathecal doses of dexmedetomidine. Materials and methods. The study included 150 patients with a mean age of 41.3 ± 8.2 years who underwent biportal endoscopic discectomy. Participants were divided into the following groups: group 1 (n = 30) — intrathecal administration of 2.5 ml bupivacaine combined with intrathecal administration of 2.5 µg dexmedetomidine; group 2 (n = 30) — intrathecal use of 2.5 ml bupivacaine with intrathecal administration of 5 µg dexmedetomidine; group 3 (n = 30) — intrathecal administration of 2.5 ml bupivacaine combined with intrathecal administration of 10 µg dexmedetomidine. In the groups, the sensory and motor status of patients and the level of analgesia were assessed. Results. The time of a SB onset was 22.78 ± 2.04 % higher in group 1 than in group 2 and 37.42 ± 2.75 % higher compared to group 3. The time of a MB onset in group 1 was 9.16 ± 1.32 % higher than in group 2 and 20.17 ± 2.36 % higher compared to group 3. In group 1, the time of a two-segment sensory regression was 21.38 ± 2.18 % lower than in group 2 and 36.40 ± 2.81 % lower than in group 3. The duration of a MB in group 3 was 18.23 ± 2.21 % higher compared to group 2 and 42.39 ± 3.05 % higher than in group 1. In group 3, the indicators of differential analgesia were 110.74 ± 4.53 % higher compared to group 2 and 202.39 ± 5.72 % higher than in group 1. Conclusions. Increasing the intrathecal dose of dexmedetomidine resulted in a reduction in the time of a sensory block onset, while the duration of a motor block increased. The indicators of analgesia duration also directly proportionally increased with the escalation of dexmedetomidine dosage.